Investigating Public Hesitation In Paying Taxes - Lenny Krisnawati (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2021)
Taxes are the biggest contributor to the state budget portion, but unfortunately the level of publicawareness in paying taxes is still very low. The purpose of this study is to investigate the causesof public hesitation in reporting the Annual Tax Return (SPT) and making tax payments, especiallyfor non-employee taxpayers at KPP Pratama Denpasar Timur (Denpasar Timur Tax Office). Thisresearch uses a qualitative approach method with purposive sampling technique. The location ofthis research is at Denpasar Timur Tax Office. The reason for choosing this location is because theDenpasar Timur Tax Office is located in the center of Denpasar city which has a large number oftaxpayers with various business classifications, and for the tax year 2018 to 2020 there has been asignificant decrease in the number of annual tax returns and tax payments from previous years.Data collection was carried out by in-depth interviews and through virtual interviews, observationsand document analysis. The interviewees in this study were non-employee individual taxpayerswho were registered at KPP Pratama Denpasar Timur with the criteria of obeying the payment andreporting of Annual SPT, often late in making payments and reporting of Annual SPT, andtaxpayers with the criteria of never making payments and reporting the Annual SPT. From theresearch results, data shows that public doubts in paying taxes are influenced by the absence ofdirect remuneration received by taxpayers, the covid-19 pandemic that paralyzed most of thecommunity's economy, limited knowledge and understanding of taxation and the limited ability oftaxpayers to utilize online facilities which has been provided by the Directorate General of Taxes